FAKTOR-FAKTOR YANG MEMPENGARUHI MUZAKKI DALAM MENYALURKAN ZAKAT PERNIAGAAN SECARA LANGSUNG (Studi Kasus di Pasar Beurenuen Kabupaten Pidie) - Ibrahim Ibrahim (STISNU Aceh, 2022)
The existence of traders who distribute their business zakat directly causes the Baitul Mal institution to be ineffective in managing and distributing zakat optimally. The potential for trade zakat must be empowered so that poverty and unemployment can be overcome. Zakat plays an important role in improving the quality of human resources. The potential for zakat owned by Aceh reaches Rp. 1.3 trillion, but in fact the absorption of zakat funds only reaches Rp. 192 billion in 2016. The occurrence of a large gap between potential zakat and the value of zakat collected indicates that there are some muzakki who distribute zakat directly. This study aims to determine the factors that influence muzakki in channeling business zakat directly and knowledge of how muzakki distribute business zakat directly. The type of research used is qualitative research while data analysis is done by means of descriptive analysis. The results of the analysis show that the factors that influence muzakki in channeling trade zakat directly are mustahik zakat at the muzakki's place of residence, lack of socialization carried out by Baitul Mal, and the absence of Baitul Mal Gampong and Settlements. Meanwhile, the knowledge of muzakki at the Beureuneun market in Pidie Regency regarding the procedures for channeling zakat is very good, they often distribute business zakat themselves by involving people who are able to provide an understanding of how to distribute business zakat directly.